Heat loss coefficients computed for floating PV modules. (27th July 2021) - Lindholm, Dag; Kjeldstad, Torunn; Selj, Josefine; Marstein, Erik Stensrud; Fjær, Hallvard Gustav
Abstract: For floating PV (FPV), the operating temperature of the PV modules has been a major source of uncertainty. As the operating temperature of PV modules affects their efficiency, knowledge of this parameter is critical in order to perform accurate energy yield assessment (EYA). This uncertainty is reflected in the scientific literature but has also hampered the bankability and realization of commercial FPV projects. Our work proposes a model that computes both the efficiency of heat loss to the environment for a given FPV technology and the operational cell temperature, needed to compute the module efficiency. The suggested model is applicable to different FPV technologies. We show that PV modules that are not in direct thermal contact with water have similar heat loss behavior as land‐based PV. We thereafter investigate a specific technology in which the modules are mounted on a membrane resting directly on the water body. The model is validated against actual production and weather data from deployed FPV systems. Our results show that the water temperature impacts both FPV technologies, however to a smaller degree for the air‐cooled system, where the wind is of greater influence. When in direct thermal contact with water, the water body provides superior cooling, and the resulting U‐value of about 86.5 W/m 2 K is significantly larger than typical values reported for land‐based modules. Abstract : For floating PV (FPV) technology, the operating temperature of the PV modules has been a major source of uncertainty. This work proposes a model that computes both the operational cell temperature and the heat loss coefficient of the FPV modules. The suggested model is applicable to the full range of different FPV technologies, from pontoon‐based FPV technologies to modules mounted to a floating membrane allowing for high thermal contact between the module and the water.